DYNAMIC AND STRUCTURE FORECASTING OF CASH TURNOVER - S. V. Mishenko (Фінансово-кредитна діяльність: проблеми теорії та практики)
In the article it was researched the main tendencies and factors of the dynamic of volume and structure of cash money circulation in Ukraine, it was grounded the scientific method to forecasting  the dynamic and structure of cash money circulation on the basis of using the regressive models.